(untitled) (Palíndromo, 2014)
This paper aims to do an image reading of a one thousand cruzeiros banknote, launched in 1977, designed by Aloisio Magalhães, which became a cultural reference in Brazil. The article is based on the image reading method by Sandra Ramalho Oliveira, in her article “Imagem também se lê” (2006), starting with the visual scanning, followed by deconstruction and elaboration of visual patterns, the redefinition of the constituent elements; relational procedures between elements; reconstruction of meaning effects; proceeding to the tireless transit between elements, procedures, block elements, whole and parts, visual and image schema, and finally presenting data image identification. Besides, it makes use of other references, related reading not only image but also the visual design and its history in Brazil in order to contextualize the work and its author.